Pengaruh Keanekaragaman Mangrove di Pulau Sibu Kecamatan Oba Utara Kota Tidore - Fadila Suparto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Mangroves are one of the Step ecosystems, because they cover 2% of the earth's surface. Indonesia is the largest mangrove ecosystem area in the world. This ecosystem has a very important ecological, socio-economic, and socio-cultural role; for example maintaining coastal stability and abrasion, fish resources and other biodiversity. Mangrove on Sibu Island is also one of the natural forests in the mangrove vegetation which is sought based on research, namely mangrove plants starting from saplings and seedlings in the diameter of the trunk